2011
DOI: 10.3324/haematol.2010.037515
|View full text |Cite
|
Sign up to set email alerts
|

Normal ranges and genetic variants of antithrombin, protein C and protein S in the general Chinese population. Results of the Chinese Hemostasis Investigation on Natural Anticoagulants Study I Group

Abstract: The online version of this article has a Supplementary Appendix. BackgroundInherited deficiency of antithrombin, protein C and protein S, three important, naturally occurring coagulation inhibitors, might play a major role in the occurrence of venous thromboembolism in Chinese. The establishment of age-and gender-related normal ranges of these inhibitors is crucial for an accurate diagnosis of these deficiencies. Design and MethodsWe designed a prospective cross-sectional study recruiting healthy adults from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 51 publications
6
42
5
Order By: Relevance
“…In both types of assays, PC in patient's plasma is activated with an activator derived from the venom of a specific snake (Protac) followed by evaluation of APC activity employing either a plasma-based activated partial thromboplastin time (aPTT) assay or a synthetic peptide-based chromogenic assay. 14,15 In a recent study aimed at establishing the normal range of PC in the healthy population, we identified a healthy subject whose PC:Ag and PC:A levels were 65%, 50% (chromogenic assay), and 36% (clotting assay) of the normal range, respectively. 15 Noting a lack of family history of VTE for the proband, we decided to determine whether a mutation in the PC gene (PROC) was responsible for this apparent type II PC deficiency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both types of assays, PC in patient's plasma is activated with an activator derived from the venom of a specific snake (Protac) followed by evaluation of APC activity employing either a plasma-based activated partial thromboplastin time (aPTT) assay or a synthetic peptide-based chromogenic assay. 14,15 In a recent study aimed at establishing the normal range of PC in the healthy population, we identified a healthy subject whose PC:Ag and PC:A levels were 65%, 50% (chromogenic assay), and 36% (clotting assay) of the normal range, respectively. 15 Noting a lack of family history of VTE for the proband, we decided to determine whether a mutation in the PC gene (PROC) was responsible for this apparent type II PC deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In a recent study aimed at establishing the normal range of PC in the healthy population, we identified a healthy subject whose PC:Ag and PC:A levels were 65%, 50% (chromogenic assay), and 36% (clotting assay) of the normal range, respectively. 15 Noting a lack of family history of VTE for the proband, we decided to determine whether a mutation in the PC gene (PROC) was responsible for this apparent type II PC deficiency. Genetic analysis revealed that the proband has a heterozygous missense mutation in PROC leading to substitution of Thr-315 of the PC heavy chain with Ala. 15 In this study, we expressed this PC mutant in HEK-293 cells and purified it to homogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of heterozygous ProS deficiency is 2-8% in thrombosis patients in Caucasian populations [15], whereas the prevalence in the general population is estimated to be 0.03-0.13% in Caucasians and 0.06-1.12% in Southeast Asians [16][17][18]. Familial and case-control studies suggest that PSD is associated with a 2.5-to 11-fold increased risk of venous thrombosis [15,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated prevalence of the heritable PC deficiency is reported ranging from 0.2 to 0.5% (Esmon, 1987;Miletich et al, 1987). Many individuals affected with PC deficiency from a heterozygous mutation remain asymptomatic for life (Miletich et al, 1987;Zhu et al, 2011). The prevalence of symptomatic hereditary PC deficiency in the population is estimated between 1:16,000 and 1:36,000 (Formstone et al, 1996).…”
Section: Introductionmentioning
confidence: 99%